Measurement of Technology Capability with Technometric Methods: Case Study at Batik Anugerah, Bangkalan, Madura Island - Indriartiningtias, Retno (Metris: Jurnal Sains dan Teknologi, 2021)
Tanjung Bumi is a village located in Tanjung Bumi Subdistrict, Bangkalan District where most of the population has a small and medium industry producing Madura batik. The object of research was carried out at Batik Anugerah. The study was conducted to determine the level of technological sophistication carried out during the production process. The study was conducted on four components including technoware, humanware, software and infoware. Based on the four components, the TCC (Technology Contribution Coefficient) value will be included in the semi-modern category.